Reviews and Responses for impunity: Enforcing Physical Unit Consistency at Definition Time in Python - Spinielli, Enrico; Sun, Junzi; Chevrot, Antoine; Olive, Xavier; Strohmeier, Martin (Journal of Open Aviation Science, 2023)
See detail reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2023.7071